Ang Wikang Filipino sa loob at labas ng akademya't bansa unang sourcebook ng Sangfil 1994-2001 - Santos, Benilda S. 1948-.; Sanggunian sa Filipino; Philippines. National Commission for Culture and the Arts.; University of the Philippines System. Sentro ng Wikang Filipino ([Quezon City] Sanggunian sa Filipino, 2003)
Filipino language used inside and outside of school and nation.
Published with UP Sentro ng Wikang Filipino-Diliman and National Commission for Culture and the Arts.
Keywords: Filipino language; Filipino language -- Social aspects; Filipino language -- Usage